Submicron perovskite microcrystal precursor for surface functionalization suitable for inkjet printing, preparation method and application thereof
Patent Information
- Application Number
- CN202611163275.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
这不仅导致薄膜表面粗糙度(RMS)激增,在大面积组件中更会造成层间接触不良和严重的并联电阻损失,使得图案化区域的电学性能极度不均
[0018]相比于现有技术,本发明所具备的有益效果为:通过空间限域合成的方法锁定微晶尺度,利用配体工程协同调控墨水流变性和结晶动力学,消除了目前高精度钙钛矿组件喷墨打印制造中首滴效应引发的可靠性危机、电学性能和打印性能难以权衡、咖啡效应导致的形貌失控、结晶失控在长程有序性和相稳定性上的不利影响,开创喷墨打印在大面积、高性能钙钛矿光伏组件的工业化生产中发挥其数字化制造本征优势的新局面。
Abstract
Description
Technical Field
[0001] This invention relates to the field of submicron perovskite microcrystals, specifically to a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, its preparation method, and its application. Background Technology
[0002] As perovskite solar cells (PSCs) move from laboratory research to pilot production lines and industrialization, the demand for refined and patterned fabrication processes is becoming increasingly prominent. Inkjet printing, as a contactless, fully digitally defined additive manufacturing process, is considered a key technology for the fabrication of next-generation high-precision perovskite modules due to its extremely high material utilization, flexible patterning capabilities (such as precise filling of P1 / P2 / P3 scribe lines), and high compatibility with flexible substrates. In inkjet printing, the rheological properties and stability of the precursor ink directly determine the print quality. Traditional inkjet inks typically use halide salts (such as PbI2 and FAI) directly dissolved in organic solvents. However, the physical process of inkjet printing involves ultra-high frequency extrusion jetting from micron-sized nozzles (typically 10-30 μm) and extremely rapid drying of picoliter (pL) level droplets on the substrate. This unique processing environment places almost stringent requirements on the intrinsic quality of the ink.
[0003] Although inkjet printing performs well in small-area patterning, existing technologies still face the following deep-seated technical bottlenecks in the large-scale continuous production of high-efficiency perovskite photovoltaic devices: 1. Physical stability and the "first drop effect" triggering a nozzle reliability crisis: Inkjet printing relies on pressure waves generated by piezoelectric ceramics to expel droplets. Current technologies using traditional microcrystalline precursors have particle sizes (typically greater than 500 nm) on the same order of magnitude as the nozzle orifice diameter, making them highly susceptible to mechanical clogging. Even more problematic is that traditional salt-dissolved inks are in a thermodynamically metastable state at the nozzle. During printing intervals, trace amounts of solvent evaporate from the nozzle, leading to localized solute supersaturation and the precipitation of solid crystals. This "first-drop effect" causes jet trajectory deflection, an increase in satellite droplets, and even irreversible printhead damage, severely limiting continuous operation time on the production line.
[0004] 2. The dilemma of balancing "electrical properties" and "printing performance" in rheological control: Inkjet printing requires inks with specific viscosities (4-20 cP) and surface tensions (25-35 mN / m) to form stable droplets. However, perovskite precursor solutions are inherently low-viscosity ionic liquids. To achieve the printing window, existing technologies commonly introduce polymers (such as PEO, PVP, or polyvinylpyrrolidone) as thickeners. These polymers are typically insulating and difficult to completely remove during subsequent low-temperature annealing processes. Their residues at the perovskite grain boundaries form significant charge transport barriers, substantially reducing carrier mobility and resulting in device fill factor (FF) and overall efficiency (PCE) that are significantly lower than those of devices fabricated by spin coating.
[0005] 3. The "coffee ring effect" and morphology loss of control during the drying process of picoliter droplets: Inkjet printing produces extremely small droplets, with evaporation rates at the droplet edges far exceeding those at the center. This evaporation rate gradient triggers a strong outward fluid motion (Marangoni flow), pushing the solute towards the droplet edges. In existing technologies, due to the lack of effective control over internal fluid resistance, the solute accumulates at the edges, forming a distinct "coffee ring" morphology. This not only leads to a surge in film surface roughness (RMS) but also causes poor interlayer contact and severe parallel resistance loss in large-area components, resulting in extremely uneven electrical performance in the patterned regions.
[0006] 4. Limitations of crystallization kinetics and phase purity risks at the microscale: Within a single picoliter of droplet, the crystallization process is completed within seconds. Traditional inks exhibit homogeneous nucleation, with the formation of nucleation sites being highly random. Due to the lack of nucleation centers, the droplet readily forms disordered, oriented small grains during rapid drying, and may even produce non-photoactive yellow phase impurities. This microscopic crystallization uncontrolled process means that the light-absorbing layer prepared by inkjet printing is far inferior to that prepared by processes with "seed-induced" characteristics in terms of long-range order and phase stability, becoming a critical technical limitation on the lifespan of inkjet-printed perovskite solar cells.
[0007] In summary, inkjet-printed perovskite solar cells face a dilemma of balancing printing reliability and thin film quality. Existing technologies lack an "advanced intermediate" that can simultaneously provide rheological regulation, intrinsic high purity, and nucleation induction capabilities, hindering inkjet printing from fully leveraging its inherent advantages in digital manufacturing for the industrial production of large-area, high-performance perovskite photovoltaic modules. Summary of the Invention
[0008] The purpose of this invention is to provide a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, its preparation method and application, so as to solve the problems raised in the background art.
[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, comprising the following steps: S1. Prepare a saturated solution of the precursor of appropriate concentration, introduce the ligand, and obtain a mixture; S2. The mixture is confined in a closed space, and crystallization is induced by reverse temperature crystallization combined with ultrasonic cavitation process. The precipitated crystal nuclei are strictly limited to the submicron level size. S3. The precipitated crystals are filtered at high temperature and washed in a circulating manner to obtain surface-functionalized submicron perovskite microcrystal precursor powder.
[0010] Preferably, in step S1, high-purity lead iodide (PbI2) and formamidine (FAI) are dissolved in γ-butyrolactone (GBL) at a molar ratio of 1:1 to 1:1.2 to obtain a saturated precursor solution. A mixed solution is obtained by introducing 0.5-2.0% by mass of branched surface functionalized ligands into a saturated precursor solution system.
[0011] Preferably, the branched surface functionalized ligand is isobutylammonium iodide or branched octylammonium iodide.
[0012] Preferably, in step S2, the mixture is placed in a crystallization vessel, and ultrasound with a frequency of 20-40kHz is applied during the heating process to 110-130℃ to obtain quasi-colloidal microcrystals with a surface highly covered by a ligand layer.
[0013] Preferably, the temperature is increased at a rate of 3°C / min in step S2; During the heating process, the branched ligands are dynamically adsorbed on the microcrystal growth interface through the steric hindrance effect, which increases the nucleation rate and inhibits the crystal ripening to the micron scale. The crystal particle size is controlled between 50-100 nm.
[0014] Preferably, in step S3, anhydrous ethanol and n-hexane are used to circulate and wash the precipitated crystals and then vacuum dry them at 60°C. By utilizing the self-purification effect during the crystallization process to remove trace metal ions, microcrystalline powder with a strict component ratio and 100% black phase purity is obtained.
[0015] A surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing is obtained by the above-described preparation method of a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing.
[0016] An application of a surface-functionalized submicron perovskite microcrystalline precursor adapted for inkjet printing, wherein inkjet printing ink is prepared using the aforementioned surface-functionalized submicron perovskite microcrystalline precursor adapted for inkjet printing. Preferably, the surface-functionalized submicron perovskite microcrystal precursor is dispersed in a mixed solvent of N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO), and then subjected to low-speed magnetic stirring at 25°C for a dissolution time of 55 min to obtain a semi-dissolved seed crystal rheology self-regulating ink. Rheology-adjustable ink is printed using industrial-grade piezoelectric printheads.
[0017] Preferably, N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO) are mixed at a volume ratio of 8:2; The magnetic stirrer rotates at 200 rpm. The orifice diameter of the industrial-grade piezoelectric nozzle is 20μm.
[0018] Compared with existing technologies, the beneficial effects of this invention are as follows: by locking the microcrystal scale through spatial confinement synthesis, and by utilizing ligand engineering to synergistically regulate ink rheology and crystallization kinetics, this invention eliminates the reliability crisis caused by the first drop effect, the difficulty in balancing electrical and printing performance, the morphological out-of-control caused by the coffee effect, and the adverse effects of crystallization out-of-control on long-range order and phase stability in the current high-precision perovskite module inkjet printing manufacturing. This creates a new situation in which inkjet printing can give full play to its inherent advantages in digital manufacturing in the industrial production of large-area, high-performance perovskite photovoltaic modules. Detailed Implementation
[0019] Example 1
[0020] This invention discloses a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, its preparation method, and its applications. The core focus is on how to lock the microcrystal size through ligand engineering and achieve rheological adaptation to the ink.
[0021] The preparation method includes the preparation of a saturated precursor solution and the introduction of ligands, spatially confined induced crystallization, cyclic washing, and component locking. First, the saturated precursor solution is prepared: high-purity lead iodide (PbI₂) and formamidine (FAI) are dissolved in γ-butyrolactone (GBL) at a molar ratio of 1:1.2 to obtain a saturated precursor solution. Next, ligands are introduced: 0.5-2.0% by mass of a branched surface-functionalized ligand is introduced into the saturated precursor solution system to obtain a mixture. The branched surface-functionalized ligands added here are preferably isobutylammonium iodide or branched octylammonium iodide. Then, spatially confined induced crystallization is performed: the previously obtained mixture is placed in a closed crystallizer, and a "reverse-temperature crystallization synergistic ultrasonic cavitation" process is used, i.e., ultrasonic waves are applied during the heating process. Specifically, the temperature is increased to 120℃ at a rate of 3℃ / min, while ultrasound at a frequency of 40kHz is applied. Branched ligands are dynamically adsorbed onto the microcrystal growth interface through steric hindrance, significantly increasing the nucleation rate and inhibiting crystal ripening to the micrometer scale. This results in quasi-colloidal microcrystals with a highly ligand-covered surface, and the precipitated nuclei are strictly limited to submicrometer sizes. Finally, the crystals are circulated, washed, and their composition locked: the precipitated crystals are filtered at high temperature, circulated and washed with anhydrous ethanol and n-hexane, and then vacuum-dried at 60℃. The self-purification effect during crystal formation removes trace metal ions, yielding microcrystalline powder with a strict composition ratio and 100% black phase purity. The resulting surface-functionalized submicron perovskite microcrystalline precursor powder has a particle size much smaller than the 20μm diameter of the subsequent industrial-grade nozzle (it should be within the 10-30μm range), and the submicron-sized precursor black phase microcrystalline particles possess high chemical purity and physical stability. According to the scanning electron microscope (SEM), the average particle size of the obtained microcrystals is 68±12nm (the target particle size of the crystals is controlled within an average particle size of 50nm-100nm), and the XRD test shows a highly pure black phase with no yellow phase peaks.
[0022] Based on the aforementioned microcrystalline particles, functionalized ligands on their surface are used to replace traditional insulating polymer thickeners, achieving precise adaptation of printing characteristics. The prepared submicron-sized precursor black-phase microcrystalline particles are applied to the preparation of rheology-modified inks for inkjet printing equipment and subsequent component molding and printing. A high-boiling-point, low-polarity solvent system is used for special dissolution of the microcrystalline particles. Specifically, the surface-functionalized submicron perovskite microcrystalline precursor is dispersed in a mixed solvent of N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO) at a volume ratio of 8:2. The mixture is then subjected to low-speed magnetic stirring at 200 rpm at 20-28°C (preferably 25°C) for 55 minutes to obtain a semi-dissolved seed crystal state of rheology-modified ink. The rheology-modified ink is then printed using an industrial-grade piezoelectric printhead with a 20 μm aperture. The key feature of the entire process is the dispersion of surface-functionalized submicron perovskite microcrystal precursor powder in a mixed solvent, exhibiting unique non-Newtonian fluid properties controlled by ligand-induced rheology. The branched ligands on the microcrystal surface and the molecules of the mixed solvent form a transient hydrogen bond network or van der Waals crosslinking, giving the ink a relatively high viscosity of 11.2 cP under static conditions (target 8-15 cP), forming a viscosity self-regulating mechanism to ensure that the precursor particles do not settle. During printing, the ink undergoes shear thinning. As the ink is squeezed through the nozzle by the piezoelectric ceramic, it is in a high-shear state, the weak gel network breaks down instantaneously, and the viscosity drops to 5.4 cP (the optimal window for inkjet printing is 4-6 cP), ensuring that droplets are ejected smoothly without creating satellite droplets. Non-equilibrium micro-dissolution control was employed, utilizing the high specific surface area of submicron microcrystals to induce a kinetically semi-dissolved state. Dynamic light scattering (DLS) measurements revealed that the ink retained 4.2% by mass of submicron-sized colloidal clusters (the target should be 3-8% by mass), preserving microcrystal seeds and forming an ideal semi-dissolved seed crystal state. These pre-reserved microcrystal seeds in the ink are crucial for resolving morphological distortion during droplet drying. Optimized jetting parameters, controlling the waveform of the piezoelectric nozzle drive pulse, maintained a droplet volume of 10-30 pL and ensured the jetting frequency remained within the 1-10 kHz range. After the ink liquid deposited on the substrate, it entered a vacuum-assisted or hot-air-assisted drying zone, forming a droplet drying and coffee ring suppression mechanism. The submicron-sized microcrystal seeds retained in the ink act as fluid crosslinking points, significantly increasing the rheological resistance within the droplet and counteracting Marangoni flow caused by rapid evaporation at the edges. The solute was effectively anchored in the droplet landing area, thereby eliminating the coffee ring morphology and achieving nanometer-level smoothness of the film thickness within the patterned region. In inkjet printing film formation, a seed crystal control process is used to suppress fluid migration and guide heterogeneous nucleation. During the annealing stage, uniformly distributed submicron-sized microcrystals serve as in-situ nucleation centers, inducing explosive crystallization of the surrounding solute. The nucleation density is determined by the pre-placed microcrystal seeds, resulting in a film with highly consistent grain size orientation and no residual yellow phase.
[0023] Continuous printing tests were conducted using a 20μm nozzle. The ink exhibited excellent stability; during 72 hours of continuous printing, no nozzle clogging occurred, and the first-drop effect deviation rate was less than 1.5%. The printed droplets spread and dried rapidly on the substrate. Due to the anchoring effect of the microcrystalline seeds, the film edges were sharp, completely eliminating the coffee ring morphology. The root mean square roughness (RMS) of the film surface was only 12.4 nm, and the final small-area battery achieved an efficiency of 23.92% and a fill factor (FF) as high as 81.5%.
[0024] Example 2
[0025] The difference from Example 1 is that no branched ligands were added during the precursor solution synthesis stage, and no ultrasonic intervention was applied subsequently. It was prepared solely by conventional reverse temperature crystallization and served as a size control comparative example of Example 1.
[0026] Experimental results show that the particle size distribution of the obtained microcrystals is extremely uneven, with an average particle size of 540nm±120nm.
[0027] During the ink mixing process, despite using the same solvent system, the ink showed obvious bottom sedimentation after standing for 2 hours due to the large particle size and lack of surface repulsion protection.
[0028] In inkjet printing tests, frequent needle misalignment and nozzle mechanical clogging occurred after only 4.5 hours of operation.
[0029] Furthermore, due to the lack of an effective rheological self-regulation mechanism, obvious solute accumulation appeared at the edges of the printed pattern, with a film thickness deviation as high as 45 nm, resulting in a fill factor FF of only 71.2% for the prepared small-area battery and a significant drop in efficiency to 19.5%.
[0030] Example 3
[0031] The ink was directly mixed with conventional halide salts, using a common method of direct dissolution of FBI2 and FAI in existing technologies. Equimolar amounts of FBI2 and FAI powders were directly dissolved in a mixed solvent of N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO) from Example 1. The solution was heated and stirred at 60°C until complete decomposition (molecular level). Testing revealed that the ink viscosity was only 3.1 cP, far below the optimal window for inkjet printing, resulting in numerous satellite droplets and extremely poor pattern definition accuracy during the jetting process. Furthermore, during film formation, the absence of any microcrystalline seeds in the ink led to strong Marangoni flow during drying. Stepwise analysis showed that the film exhibited a typical "coffee ring" morphology: an edge thickness of 650 nm and a center thickness of only 280 nm. This extreme inhomogeneity resulted in severe internal short circuits in large-area components, with a PCE efficiency of only 17.8%. In addition, ICP-MS analysis revealed the presence of metallic impurities such as Ca.2+ and Mg 2+ The content was as high as 92 ppm, which is much higher than the 4 ppm after recrystallization and purification in Example 1.
[0032] Analysis of Examples 1-3 leads to the conclusion that the present invention, through the pre-synthesis of submicron-sized microcrystals, increases the purity of raw materials from 99.9% to over 99.99%, resulting in an increase of approximately 45mV in the open-circuit voltage (Voc) compared to the traditional salt method (Example 3), significantly improving purity and stability. In Example 1, the particle size of approximately 68nm exhibits excellent compatibility with the printhead, and its continuous working life is more than 16 times that of traditional large-size microcrystals (Example 2). Furthermore, it addresses the crystallization blockage caused by solvent evaporation in salt-method inks, significantly improving the reliability of ink printing. Example 1 successfully controlled the RMS roughness of the film to within 15nm using 4.2% by mass of microcrystal seeds, achieving near-perfect smoothness compared to the coffee ring distortion morphology of Example 3, scientifically controlling the film morphology. Relying on additive-free, autonomous rheological control, Example 1 maintains high printing performance while ensuring smooth charge transport, resulting in a 10% absolute increase in the fill factor (FF) compared to the method using conventional polymer thickeners, demonstrating significant performance gains.
[0033] In summary, this invention addresses the unique characteristics of inkjet printing (IJP) technology by providing specific solutions to the four major defects mentioned in the background art. Specifically, through the design of surface-functionalized submicron-level microcrystals, it demonstrates significant advantages in resolving the conflict between printing reliability and film quality.
[0034] 1. Eliminates nozzle clogging and the "first drop effect," significantly improving the stability of continuous production line operation: By locking the microcrystal size to the 50nm-100nm level, which is much smaller than the 10μm-30μm micropore size of the inkjet head, the risk of mechanical clogging is eliminated on a physical scale.
[0035] Combined with the strong steric hindrance provided by the surface-branched ligands, the ink exhibits extremely high dispersion stability at the nozzle, effectively suppressing solute precipitation and crystallization caused by trace solvent evaporation. This completely solves the "first-drop effect" that plagues inkjet printing, ensuring that the nozzle maintains a precise jet trajectory and droplet volume even after long periods of standby or intermittent printing, greatly extending the printhead's maintenance cycle and lifespan.
[0036] 2. Achieved additive-free rheological control, ensuring the intrinsic electrical quality of the light-absorbing layer: Unlike existing technologies that require the introduction of insulating polymers (such as PVP and PEO) to adjust viscosity, this invention utilizes the interaction between functionalized ligands on the microcrystalline surface and solvent molecules to achieve "self-regulation" of ink rheological properties.
[0037] This "self-regulating" mechanism endows the ink with excellent non-Newtonian fluid properties (shear-thinning), maintaining high viscosity to prevent sedimentation under static conditions while reducing viscosity during jetting to ensure smooth droplet flow. Because it contains no harmful insulating polymer residues, the resulting perovskite film has cleaner grain boundaries and minimal charge transport resistance. Experimental results show that its carrier mobility is more than 40% higher than inks containing polymer additives, significantly optimizing the device's fill factor (FF).
[0038] 3. Physically suppressing the "coffee ring effect" to achieve large-area film formation with nanoscale smoothness: This invention utilizes submicron-sized microcrystal seeds retained in ink through a "partial dissolution" process as "nanoanchors" within the fluid, thereby reconstructing the droplet evaporation dynamics.
[0039] These microcrystalline seeds effectively counteract the solute migration towards the edges driven by the Marangoniflow during droplet drying through physical damping. This "seed anchoring" mechanism eliminates the coffee ring morphology at its source, allowing the film thickness deviation of the printed patterned areas (such as the P2 groove filling area) to be controlled within ±2nm. The smooth film surface not only optimizes interlayer contact but also significantly reduces parallel leakage current caused by uneven film thickness, thereby improving the parallel resistance (Rsh) of the component.
[0040] 4. Lowering the nucleation energy barrier and inducing directional crystallization improves the purity and stability of the thin film phase. The pre-synthesized microcrystals are already stable α-phase structures, and they are distributed extremely evenly in the ink as in-situ seed crystals.
[0041] By transforming the crystallization process from random "homogeneous nucleation" to ordered "heterogeneous nucleation," the nucleation energy barrier is significantly reduced, enabling the film to achieve explosive crystallization under lower temperature annealing conditions. This avoids thermal damage to the underlying charge transport layer and flexible substrate caused by high temperatures, thus optimizing the energy barrier.
[0042] The lattice template effect of the pre-placed seed induces the surrounding solute to grow along a specific direction, forming a high-quality light-absorbing layer with highly consistent orientation and uniform grain size distribution. This completely eliminates the generation of the non-photoactive yellow phase (δ-phase), intrinsically enhancing the long-term operational stability of the device and realizing structural inheritance.
[0043] In addition, while addressing the four major shortcomings mentioned above, it also achieves extremely high standards of digital process flexibility and component accuracy: By using a single-component microcrystalline powder as a precursor source, the risk of component drift during the mixing and dissolution of multiple salt raw materials is avoided. This "single-substance precursor" simplifies the ink formulation process and greatly improves the consistency between different batches of ink. Combined with the digital definition function of inkjet printing, this invention can achieve the deposition of perovskite functional layers with complex shapes and high edge sharpness, and is particularly suitable for precision processing scenarios such as flexible folding components, semi-transparent photovoltaic windows, and tandem solar cell top cells, making it highly valuable for industrial application.
[0044] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, characterized in that: The steps include S1. Prepare a saturated solution of the precursor of appropriate concentration, introduce the ligand, and obtain a mixture; S2. The mixture is confined in a closed space, and crystallization is induced by reverse temperature crystallization combined with ultrasonic cavitation process. The precipitated crystal nuclei are strictly limited to the submicron level size. S3. The precipitated crystals are filtered at high temperature and washed in a circulating manner to obtain surface-functionalized submicron perovskite microcrystal precursor powder.
2. The method for preparing surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing according to claim 1, characterized in that: In step S1, high-purity lead iodide (PbI2) and formamidine (FAI) are dissolved in γ-butyrolactone (GBL) at a molar ratio of 1:1 to 1:1.2 to obtain a saturated precursor solution. A mixed solution is obtained by introducing 0.5-2.0% by mass of branched surface functionalized ligands into a saturated precursor solution system.
3. The method for preparing surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing according to claim 2, characterized in that: The branched surface functionalized ligands are isobutylammonium iodide or branched octylammonium iodide.
4. The method for preparing surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing according to claim 1, characterized in that: In step S2, the mixture is placed in a crystallization vessel, and ultrasound with a frequency of 20-40kHz is applied during the heating process to 110-130℃ to obtain quasi-colloidal microcrystals with a surface highly covered by a ligand layer.
5. The method for preparing surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing according to claim 4, characterized in that: In step S2, the temperature is increased at a rate of 3℃ / min; During the heating process, the branched ligands are dynamically adsorbed on the microcrystal growth interface through the steric hindrance effect, which increases the nucleation rate and inhibits the crystal ripening to the micron scale. The crystal particle size is controlled between 50-100 nm.
6. The method for preparing surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing according to claim 1, characterized in that: In step S3, the precipitated crystals are circulated and washed with anhydrous ethanol and n-hexane and then vacuum dried at 60°C. By utilizing the self-purification effect during the crystallization process to remove trace metal ions, microcrystalline powder with a strict component ratio and 100% black phase purity is obtained.
7. A surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, characterized in that: The surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing is obtained by the preparation method of the surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing as described in any one of claims 1-6.
8. An application of a surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing, characterized in that: Inkjet printing inks are prepared using the surface-functionalized submicron perovskite microcrystal precursors adapted for inkjet printing as described in claim 7.
9. The application of the surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing according to claim 8, characterized in that: The surface-functionalized submicron perovskite microcrystal precursor was dispersed in a mixed solvent of N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO), and the mixture was magnetically stirred at low speed at 25°C for 55 min to obtain a semi-dissolved seed crystal rheology self-regulating ink. Rheology-adjustable ink is printed using industrial-grade piezoelectric printheads.
10. The application of the surface-functionalized submicron perovskite microcrystal precursor adapted for inkjet printing according to claim 9, characterized in that: N-vinyl-2-pyrrolidone (NVP) and dimethyl sulfoxide (DMSO) were mixed at a volume ratio of 8:
2. The magnetic stirrer rotates at 200 rpm. The orifice diameter of the industrial-grade piezoelectric nozzle is 20μm.
